Pengaruh Terpaan Informasi Menikah Muda di Instagram dan Interaksi Reference Group Terhadap Minat Menikah Muda - Gebiya Efriman Putri; Agus Naryoso (Interaksi Online, 2019)
One of the social media that many interested in Indonesia is Instagram. Among dakwah activists, Instagram is used as a medium for information about getting young marriage. In addition to the use of Instagram, young marriage is also influenced by other factors, namely the reference group. This reference group often shares information about getting young marriage. Based on Article 7 paragraph 1 No.1 1974 of the Marriage Act of the Ministry of Religion of the Republic of Indonesia that the men have reached the age of 19 years and the women have reached the age of 16 to get married. This research is a quantitative study with explanatory research types. The population of this study is Diponegoro University students, men aged 19-25 years and women aged 16-21 years and have an Instagram account. Sampling was done by accidental sampling of 100 respondents. Testing is done with Ordinal Regression Test. The research shows that there is an influence between the information exposure of young married on Instagram towards the interest of young married by 13.5%. The remaining 86.5% is influenced by other factors, not examined in this study. The correlation between variables shows a sign of 0.002 because < 0.05. And research shows that there is an influence between the interaction of the reference group towards the interest of young married by 22.4%. The rest, which is equal to 77.6% is influenced by other factors, not examined in this study. The correlation between variables shows a sign of 0,000 because < 0.05. This explains how there is an influence between the information exposure of young married people on Instagram and the interaction of reference groups towards the interest in young marriage, although with little influence. Other influences can be caused by other factors such as exposure to Indonesian information without dating and financial quality.